Technical Considerations for the Use of REBOA in the Management of Placenta Accreta Spectrum - Nieto-Calvache, Albaro José; Rodríguez, Fernando; Ordoñez, Carlos A; Cardona Astaiza, Adriana; Carbonell, Juan Pablo; Vergara-Galliadi, Lina María; Sinisterra-Díaz, Stiven Ernesto; Bryon, Adriana Messa (Journal of Endovascular Resuscitation and Trauma Management, 2022)
In recent years, the use of resuscitative endovascular balloon occlusion of the aorta (REBOA) has become popular to prevent or treat massive bleeding due to placenta accreta spectrum (PAS). There are multiple variations in the use of REBOA in this context, and although the experience of vascular surgeons with aortic balloons is extensive, there are particularities in the management of these devices in the obstetric population that deserve to be discussed. We discuss some technical considerations or “lessons learned” in our center that may be useful for other groups starting to use REBOA for PAS. Although REBOA is a useful strategy to prevent or treat massive bleeding due to PAS, its incorporation into management protocols must be carried out in a programmed and supervised manner.